Myeloid-Derived Suppressor Cells: A New and Pivotal Player in Colorectal Cancer Progression - Yin, Kai; Xia, Xueli; Rui, Ke; Wang, Tingting; Wang, Shengjun (Frontiers in Oncology, 2020)
Colorectal cancer (CRC) remains a devastating human malignancy with poor prognosis. Of the various factors, immune evasion mechanisms play pivotal roles in CRC progression and impede the effects of cancer therapy. Myeloid-derived suppressor cells (MDSCs) constitute an immature population of myeloid cells that are typical for tumor progression. Most notably, these cells have the ability to induce strong immunosuppressive effects in tumor microenvironment (TME) and induce CRC development. Indeed, MDSCs have been shown to accumulate in tumor-bearing mice and CRC patients and thus become an obstacle for cancer immunotherapy. Consequently, numerous studies have focused on the characterization of MDSCs and their immunosuppressive capacity, and possible ways to suppress MDSCs function with different approaches. Current therapeutic approaches to target MDSCs in CRC include inhibition of their recruitment, alteration of their function, or combination other therapies including chemotherapy, radiotherapy and immunotherapy. Herein, we also summarize recent roles and mechanisms of MDSCs in CRC progression. In addition, a brief review of MDSCs-targeting approaches for potential CRC therapy is presented.